(untitled) (International Journal of Physiotherapy, 2015)
Background: Hippotherapy is a physical treatment strategy with the help of horses and refers to the use of horse’s movement as a treatment tool for children with Cerebral Palsy (CP). Hippotherapy refers to the incorporation of equine movement by physiotherapists, occupational therapists and speech therapists. The present qualitative study investigated the impacts of hippotherapy on Greek children with Cerebral Palsy from parents’ perspective due to their better understanding of child’s special needs. Methods: Semi-structured interviews were undertaken with 10 participants. An interview topic guide and introductory closed questions were used to conduct the study. Thematic analysis of the qualitative interview data was carried out. Five themes were revealed from the interview process. Results: The results of this qualitative research provides evidence that hippotherapy is a promising intervention strategy having physical and psychological benefits for children with CP. Hippotherapy improved children’s daily activities, their independence and, in general, a better quality of life has been attained, while no negative impacts has been identified. The impacts of these results were discussed in relationship with relative published research. Additionally, new insights were provided. The professionalism and qualification of clinical specialist in hippotherapy were crucial and they influence positively the results of hippotherapy. This study also provided new insights into the context of the relationship-cooperation between clinical specialist in hippotherapy and child, and the financial factor participating in a hippotherapy programme. Conclusion: Discussion concerning the clinical implications of the present findings and suggestions for future research were provided. Future research should be conducted to provide a clear definition of what hippotherapy is meaning globally.